Optimization of submerged culture for the production of naphthoquinones pigment by fusarium verticillioides - Kongsak Boonyapranai (2018)
A locally isolated fungus genus, Fusarium verticillioides., was evaluated as a potential producer of naphthoquinone pigment. Five variable growth media (type of complex media, carbon source, nitrogen source, mineral salt and initial pH of the medium) were systematically manipulated in shake flask culture to improve the yield of total naphthoquinone. The naphthoquinone production was supported by addition of peptone and yeast extract but malt extract exhibited the opposite result. Substantially, the mineral salt of K+, Na+, Mn2+, Cu2+ and Zn2+, less than 50 mg/l, were necessary for the efficient naphthoquinone production by F. verticillioides. In addition, efficiency of pigment production at various values of initial medium pH showed that the biosynthesis of naphthoquinone was regarded by initial pH and changing of medium pH. Taken together, the results indicated that the naphthoquinone pigment production for this particular strain could be maximized by using a basal growth medium consisting of 20% (w/v) of boiled white potatoes; 20 g/l glucose; 2.5 g/l yeast extract, supplemented with 5 mg/l of KH2PO4 and adjust initial medium pH at 8.0. The pigment production under the optimum condition was 13.61 mg/g-cell when cultured at 30° with agitation rate at 200 rpm for 7 days.